2017
DOI: 10.3390/app7121216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Silica Nanofluids: Reduction of Fines Migrations and Surface Modification of Berea Sandstone

Abstract: This work is aimed at addressing surface modification of berea sandstone by silica nanofluids (NFs). Three types of nanofluids were used: silica/deionized water (DIW), silica in DIW with a stabilizer fluid (3-Mercaptopropyl Trimethoxysilane) and sulfonate-functionalized silica in DIW. Core flood studies showed that application of silica nanoparticles (NPs) improved water injectivity in sandstone. The change in the measured zeta potential indicated surface modification of sandstone by application of NPs. Comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…However, increased calcite dissolution induced by low salinity interaction with chalk during flooding may lead to loss of rock integrity [43]. Previous work in our lab investigated the adsorption different silica NPs on sandstone minerals and its effect on fines migration [44]. We found the silica NPs modifies the sandstones minerals and it can be utilized to overcome the problem of formation damage induced during low salinity flooding in sandstones.…”
Section: Introductionmentioning
confidence: 89%
“…However, increased calcite dissolution induced by low salinity interaction with chalk during flooding may lead to loss of rock integrity [43]. Previous work in our lab investigated the adsorption different silica NPs on sandstone minerals and its effect on fines migration [44]. We found the silica NPs modifies the sandstones minerals and it can be utilized to overcome the problem of formation damage induced during low salinity flooding in sandstones.…”
Section: Introductionmentioning
confidence: 89%
“…One paper explores NPs for EOR applications. The paper by Abhishek et al [6] studied the potential of different silica nanofluids as surface modifying agents for Berea sandstone. Surface modification of sandstone by silica NPs has net attractive potential with fines, leading to reduction of fines migration and improvement of water injectivity.…”
Section: Nanotechnology and Nanomaterials Applications In The Oil Andmentioning
confidence: 99%
“…A variety of nanoparticle (NP) materials have been used to prepare transformer oil-based nanofluids, exhibiting different modification effects. It is found that the positive lightning impulse breakdown voltage of mineral transformer oil can be improved by 82.6% with the addition of Fe 3 O 4 nanoparticles [13]. For TiO 2 nanofluid, the breakdown voltage is increased by 23.6% [14].…”
Section: Introductionmentioning
confidence: 97%
“…Many efforts have been devoted to improve the positive breakdown voltage of transformer oil. In the past two decades, nanofluids (NFs) have attracted much attention due to their good insulating and thermal performance [12,13]. A variety of nanoparticle (NP) materials have been used to prepare transformer oil-based nanofluids, exhibiting different modification effects.…”
Section: Introductionmentioning
confidence: 99%